Biosurfactants as Anticancer Agents: Glycolipids Affect Skin Cells in a Differential Manner Dependent on Chemical Structure - Simms A. Adu; Matthew S. Twigg; Patrick J. Naughton; Roger Marchant; Ibrahim M. Banat (MDPI AG, 2022)
Melanomas account for 80% of skin cancer deaths. Due to the strong relationship between melanomas and U.V. radiation, sunscreens have been recommended for use as a primary preventative measure. However, there is a need for targeted, less invasive treatment strategies. Glycolipids such as sophorolipids and rhamnolipids are microbially derived biosurfactants possessing bioactive properties such as antimicrobial, immunomodulatory and anticancer effects. This study aimed to ascertain the differing effects of glycolipids on skin cells. Highly purified and fully characterized preparations of sophorolipids and rhamnolipids were used to treat spontaneously transformed human keratinocyte (HaCaT) and the human malignant melanocyte (SK-MEL-28) cell lines. Cell viability and morphological analyses revealed that glycolipids have differential effects on the skin cells dependent on their chemical structure. Lactonic sophorolipids and mono-rhamnolipids were shown to have a significantly detrimental effect on melanoma cell viability compared to healthy human keratinocytes. These glycolipids were shown to induce cell death via necrosis. Additionally, sophorolipids were shown to significantly inhibit SK-MEL-28 cell migration. These findings suggest that glycolipids could be used as bioactive agents with selective inhibitory effects. As such, glycolipids could be a substitute for synthetically derived surfactants in sunscreens to provide additional benefit and have the potential as novel anti-skin-cancer therapies.